Ekonomi Syariah sebagai Solusi Pengembangan Ekonomi Berkelanjutan di Kabupaten Sumbawa - Iga Mawarni; M Fahad Addi Pratama; Sasmita Adekantari; Feri Irawan (CV. Ulil Albab Corp, 2024)
In the current era of economic development complexity, sustainable development has become a critical focus for many countries, including Indonesia. The aim of sustainable development is to achieve a balance between economic growth, environmental preservation, and social justice. Meeting these challenges requires a reconstruction of economic models that can achieve long-term sustainability by integrating ethical values, including Islamic values. The Qur'an and Sunnah form the basis of Islamic sciences, guiding various aspects of life, including economics. Islamic Economics, or Shariah Economics, represents a reconstructed economic model based on Islamic principles, using revelation, reason, and ijtihad (interpretation) as foundational elements. Principles such as the prohibition of usury (riba) and efforts to ensure fair wealth distribution aim to create a sustainable and inclusive economic environment. This research employs a literature review method to elucidate how Shariah Economics can serve as a solution for sustainable economic development in Sumbawa Regency. Emphasizing financial inclusion, empowerment of SMEs, and principles of justice in economic transactions, Shariah Economics offers a significant contribution to enhancing overall societal welfare.